Attenuation of Electromagnetic Waves Using Nano Composites - Saifallah Asad Lami Daoud; Abbas Hussein Saiyou Abdul Sada; Ghaffar Yasir Jasim Hassan Alnoor; Ruwaida Qahtan Adnan Ghaydan; Taif saad Yasser manshed (Genius Journals, 2024)
Through all the prepared samples, it was found that they have a varying ability to attenuate microwaves within the (X) band (X-band) and at different ranges of frequency. Regarding the electrical properties, it is noted that there is a similarity in the behavior of the dielectric constant with the capacitance of the capacitance and for all the samples that were prepared, which indicates the similarity between the electrical conduction and polarization in ferrite materials
Keywords: Attenuation; Electromagnetic; Nano composites